Preparation of nanoporous nickelcopper sulfide on carbon cloth for high-performance hybrid supercapacitors. (20th May 2018) - Du, Dongwei; Lan, Rong; Humphreys, John; Amari, Houari; Tao, Shanwen
Abstract: In this work, nanoporous nickel-copper sulfide on carbon cloth was successfully prepared via sulfurizing the nickel-copper carbonate hydroxide precursor through an anion exchange reaction. The as-fabricated electrode exhibits a high specific capacitance of 938.6 F g −1 at a current density of 1 A g −1 and good rate capability of 76% at 10 A g −1, as well as excellent flexibility. Charge storage analysis demonstrates that the combination of surface-controlled capacitive process and diffusion-controlled Faradaic process, both contribute to the total capacitance. In addition, the good performance of the nanoporous nickel-copper sulfide can be attributed to the possible higher conductivity and porous nanostructures which offers more active sites to yield extrinsic pseudocapacitance. A hybrid supercapacitor was assembled with nickel-copper sulfide as the positive electrode and nitrogen-doped graphene as the negative electrode, delivering a high cell voltage up to 1.7 V with a maximum energy density of 35.3 Wh kg −1 and a maximum power density of 12700 W kg −1 . A red round light-emitting diode (LED) was successfully illuminated by the pouch cell composed of two Ni0.8 Cu0.2 −S//NG HSCs. The high performance we achieved suggests that the nanoporous nickel-copper sulfide has deep potential for high-performance supercapacitor applications. Graphical abstract: Nanoporous nickel-copper sulfide on carbon cloth is prepared as positive electrode materials for high-performance supercapacitors. Highlights: Nanoporous nickel-copper sulfide on carbon cloth (Ni0.8 Cu0.2 −S) was successfully prepared. Specific capacitance of 938.6 F g −1 at a current density of 1 A g −1 was achieved. Both surface and diffusion-controlled processes contribute to the total capacitance. The Ni0.8 Cu0.2 −S//NG hybrid supercapacitor was successfully assembled and the high energy and power densities were achieved.